Targeted delivery of black phosphorus nanosheets by ROS responsive complex hydrogel based on angiogenesis and antioxidant promotes myocardial infarction repair - Zhang, Jiahui; Sun, Di; Guo, Yishan; Tong, Junran; Liu, Qingyi; Gao, Ran; Wei, Yumiao; Guo, Xiaopeng (Journal of nanobiotechnology, 2024)
Myocardial infarction (MI) is one of the leading causes of death. This is attributed to the dramatic changes in the myocardial microenvironment post-MI. Therefore, effective intervention in the early stages of MI is significant for inhibiting its progression and improving cardiac function. Herein, an injectable composite hydrogel scaffold (Gel-pBP@Mg) was developed by integrating magnesium (Mg)-modified black phosphorus nanosheets (pBP@Mg) into a reactive oxygen species-responsive hydrogel (Gel). This loose and porous Gel provides a natural platform for carrying pBP@Mg. In situ, sustained release of pBP@Mg is achieved via responsive ROS degradation in the infarct site. The high ROS reactivity of Black phosphorus nanosheets (BPNSs) can effectively inhibit the progression of oxidative stress in the infarct area and reduce inflammatory response by down-regulating the NF-κB pathway. Additionally, the sustained release of Mg loaded on the surface of BPNSs can effectively promote angiogenesis in MI, which is significant for the long-term prognosis after infarction. Our developed Gel-pBP@Mg effectively blocked infarction progression and improved myocardial function by sustainably inhibiting the “oxidative stress-inflammation” reaction chain and pro-angiogenesis. This study reveals Gel-pBP@Mg composite therapeutic potential in treating MI through In vitro and In vivo studies, providing a promising modality for MI treatment. Graphical abstract